Differentially expression and function of circular RNAs in ovarian cancer stem cells - Eun Jung Sohn (BMC, 2022)
Abstract Background Circular RNAs (circRNAs) are noncoding RNAs that regulate miRNA expression; however, their functions in cancer stem cells (CSCs) are not well known. Methods To determine the function of differentially expression of circRNAs associated with ovarian CSCs, circRNA profiling was conducted using a circRNA-based microarray on sphere-forming cells derived from A2780 and SKOV3 epithelial ovarian cancer cells termed A2780-SP and SKOV3-SP compared to monolayer cells such as A2780 and SKOV3 cells, respectively. Gene Ontology (GO) enrichment and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were performed to predict the biological functions of the circRNAs expressed in CSCs. Results The circRNA-based microarray data showed that 159 circRNAs were significantly upregulated (fold change > 1.5) and 55 circRNAs were downregulated in ovarian CSCs compared to monolayer cells. GO and KEGG enrichment analysis of differentially expressed circRNAs in ovarian CSCs showed that they were mainly involved in cell cycle, histone modification, cellular protein metabolic process, cell cycle, apoptotic signaling pathway, and ubiquitin-mediated proteolysis in ovarian cancer. In addition, the hsa-circRNA000963-miRNA-mRNA regulatory network was constructed based on potential target of miRNAs. These analyses involved that the biological function of the hsa-circRNA00096/miRNA/mRNA network was involved in signaling pathways regulating pluripotency of stem cells, PI3K-Akt signaling pathway, cell cycle, p53 signaling pathway, Wnt signaling pathway, calcium modulating pathway, and production of miRNAs involved in gene silencing by miRNA. Conclusions Our data demonstrate the expression profiles of circRNAs in ovarian CSCs and suggest that circRNAs may be potential diagnostic and predictive biomarkers of ovarian cancer.